Topographies of faith : religion in urban spaces - Becci, Irene.; Burchardt, Marian.; Casanova, José. (International Studies in Religion and Society, 2013)
Based on ethnographic explorations in cities across the globe, Topographies of Faith offers a unique and compelling analysis of contemporary religious dynamics in metropolitan centers. While most scholarship on religion still sidelines questions of spatiality and scale, this book creatively draws on perspectives from urban studies to study the spatiality of religion in modern cities. It shows how globalization, transnational migration and urban expansion in big cities engender new religious forms and practices and their spatial underpinnings. Space affects urban religious diversity, religious innovations, decline or vitality. But it also shapes the relationships between religion and social equalities. Spanning distances between New York, Delhi and Johannesburg, the book also engages with issues of secularity and religious vitality in genuinely new ways.